Role of dominant microflora of Picante cheese on proteolysis and lipolysis - Freitas, A. Cristina (2011)
Four species of bacteria (Enterococcus faecium and E. faecalis, Lactobacillus plantarum and Lb. paracasei) and three species of yeasts (Debaryomyces hansenii, Yarrowia lipolytica and Cryptococcus laurentii) isolated from Picante cheese were assayed for proteolytic and lipolytic activities. The milk type (caprine or ovine), the ripening time (0–65 d) and the concentration of NaCl (0–14% (w/v)) have been studied in terms of their effects upon in vitro curdled milk. Proteolytic and peptidolytic activities were demonstrated to be high for Y. lipolytica, and at much lower levels for the other strains. Milk type, ripening time and content of NaCl appeared to be statistically significant processing factors in terms of proteolysis. Clear lipolytic activity was detected for Y. lipolytica, but release of free fatty acids to lesser extents was observed for the other strains under study. Ripening time was statistically significant for lipolysis but milk type was not. Lipolytic activities were strongly affected by NaCl content and the extent of fat hydrolysis was affected by the increase of NaCl from 0 to 7% (w/v) more than by change from 7 to 14% (w/v). In view of the experimental results, a mixed-strain starter for Picante cheese including Lb. plantarum, E. faecium (or E. faecalis) and D. hansenii (and/or Y. lipolytica) is of potential interest.